The Other Side of The Coin: Analyzing Software Encoding Schemes Against Fault Injection Attacks - Breier, Jakub (2016)
The versatility and cost of embedded systems have made it ubiquitous. Such wide-application exposes an embedded system to a variety of physical threats like side-channel attacks (SCA) and fault attacks (FA). Recently, a couple of software encoding schemes were proposed as a protection against SCA. These protection schemes are based on dual-rail precharge logic (DPL), previously shown resistant to both SCA and FA. In this paper, we analyze the previously proposed software encoding schemes against FA. Our results show that software encoding offers only limited resistance to FA. Finally, improvement to software-encoding schemes is improved. With this improvement, software encoding can serve as a common SCA and FA countermeasure with an exploitable fault probability as low as 0.0048.